Corporate Social Responsibility dan Good Corporate Governance Terhadap Nilai Perusahaan dengan Intellectual Capital sebagai Moderasi - Ningrum, Miftahul Janah Tejo; Anggraini, Dahlia Tri (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
This research aims to examine the impact of GCG and CSR on firm value, and whether IC moderates these effects. This research use data from the Indonesia Stock Exchange (IDX) for the food and beverage subsector from 2021-2023. In this research, the sample was selected through the purposive sampling method and employs descriptive statictical analysis, panel data regression, and model feasibility testing techniques. The result of this research indicate that CSR, GCG, and IC have a positive effect to Firm Value. The connection between CSR and the value of a company cannot be moderated by IC. However, it has the potential to influence the relationship between GCG and firm value. This research contributes by offering a new perspective, positioning IC as a moderating variable that can strengthen or weaken the relationship between CSR and GCG on firm value.